2002
DOI: 10.1197/aemj.9.6.561
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Canadian Clinical Probability Model for Acute Venous Thrombosis

Abstract: Objective: To validate the predictive value of the Canadian clinical probability model for acute venous thrombosis, which, to the best of the authors' knowledge, has not been done in emergency department (ED) settings outside of Canada. Methods: Demographic and clinical information, rapid D-dimer testing, and venous ultrasound imaging were obtained among patients presenting with clinically suspected venous thrombosis at a university-affiliated ED. A diagnosis of deep venous thrombosis (DVT) was made based on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
2
6
0
1
Order By: Relevance
“…Studies of serial US [109-112,120], a single full-leg US [121-124], or US as part of a diagnostic algorithm [114,116,117,125-129] have shown low rates of thromboembolism during three to six month follow up. This suggests that, although our meta-analysis has shown that US does not have perfect sensitivity for DVT (especially distal thrombus), this does not translate into high rates of adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of serial US [109-112,120], a single full-leg US [121-124], or US as part of a diagnostic algorithm [114,116,117,125-129] have shown low rates of thromboembolism during three to six month follow up. This suggests that, although our meta-analysis has shown that US does not have perfect sensitivity for DVT (especially distal thrombus), this does not translate into high rates of adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of a potential alternative diagnosis as likely or more likely than DVT, present in 40–61% of cases of suspected DVT [20,22,31,48], is a critical criterion of the Wells score, which introduces a subjective element into the assessment. If uncertainty exists about the interpretation of this item, an assumption that no alternative diagnosis exists maximizes the safety of this strategy.…”
Section: Formalized Assessment Of Ptpmentioning
confidence: 99%
“…If uncertainty exists about the interpretation of this item, an assumption that no alternative diagnosis exists maximizes the safety of this strategy. Nevertheless, this has since become the most widely used prediction rule for DVT, and several studies performed in different institutions [9,14,20,29–31,48–51], including clinical management studies [14,31,51], have validated the clinical utility of the simplified score in outpatients, and one management study has validated its utility in inpatients [52]. PTP was usually assessed either by the study physicians or emergency department physicians, but in one study [9], it was initially assessed by a vascular technologist or specialist nurse who could subsequently be over‐ridden by a physician, and in another was assessed by a trained nurse who then deferred to a physician, who decided on the likely presence or otherwise of an alternative diagnosis [31].…”
Section: Formalized Assessment Of Ptpmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivities and specifi cities of the rule (at each cutoff) refl ect how correctly the rule predicts the presence or absence of disease. We identifi ed 19 studies that evaluated clinical prediction rules for the diagnosis of DVT, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and 8 studies evaluating clinical prediction rules for the diagnosis of pulmonary embolism, [35][36][37][38][39][40][41][42] although common patients were reported in 3 studies. [40][41][42] (Supplemental Appendix 1, available online at http://www.annfammed.org/cgi/content/full/5/1/63/DC1).…”
Section: Are Clinical Prediction Rules Valuable For Diagnosing Dvt Ormentioning
confidence: 99%